Digital transformation in the cultural and creative industries : production, consumption and entrepreneurship in the digital and sharing economy - Massi, Marta, 1980- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This research-based book investigates the effects of digital transformation on the cultural and creative sectors. Through cases and examples, the book examines how artists and art institutions are facing the challenges posed by digital transformation, highlighting both positive and negative effects of the phenomenon. With contributions from an international range of scholars, the book examines how digital transformation is changing the way the arts are produced and consumed. As relative late adopters of digital technologies, the arts organizations are shown to be struggling to adapt, as issues of authenticity, legitimacy, control, trust, and co-creation arise. Leveraging a variety of research approaches, the book identifies managerial implications to render a collection that is valuable reading for scholars involved with arts and culture management, the creative industries and digital transformation more broadly"--
OCLC-licensed vendor bibliographic record.
Keywords: Cultural industries -- Technological innovations; Digital media -- Technological innovations; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Nonprofit Organizations & Charities